Financial constraints and other obstacles: are they a threat to innovation activity? - Pierre A. Mohnen; Franz Palm; Sybrand Schim van der Loeff; A. Tiwari (Center for Economic Studies and ifo Institute (CESifo), 2008)
In this paper we examine the importance of financial and other obstacles to innovation in the Netherlands using statistical information from the CIS 3.5 innovation survey. We report results on the effect of these obstacles on the firms' decision to abandon, prematurely stop, seriously slow down, or not to start an innovative project. These results are compared with those from other studies in the Netherlands and other countries. We end with a discussion of policy measures that have been taken to overcome, or at least attenuate these obstacles, such as R&D tax incentives, venture capital financing and policy mix packages.
Keywords: O31; O38; D21; 330; financial constraints; innovations; innovation policy; Innovationsmanagement; Unternehmensfinanzierung; Innovationspolitik; Niederlande; Welt